2001
DOI: 10.1177/030631201031001003
|View full text |Cite
|
Sign up to set email alerts
|

The Diabolical Symphony of the Mechanical Age:

Abstract: New technologies profoundly change our sonic surroundings, the world's soundscape. However, research dealing with the sound of technology is scarce within Science and Technology Studies (S&TS). This study argues that such a silence should be broken, since the sound of technology not only tunes our sonic environment, but has also been a highly controversial aspect of technology loaded with symbolic significance. Research into such a symbolism of sound enhances our understanding of the responses to technolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(8 citation statements)
references
References 10 publications
0
7
0
1
Order By: Relevance
“…The significance of city noise to the human psyche cannot be underestimated. An Association for the Suppression of Street Noises, founded in the 1890s, wielded vigorous campaigns that were widely reported on in the newspapers of the times (Bijsterveld, 2003). A 1906 column in the Illustrated London News about the 'Nervous Age' reported that doctors were complaining to Parliament about the "injurious effects on the nervous system produced by the excessive noise of our streets" ( [Anon.…”
Section: The Poetics Of Noise In Italian Futurismmentioning
confidence: 99%
“…The significance of city noise to the human psyche cannot be underestimated. An Association for the Suppression of Street Noises, founded in the 1890s, wielded vigorous campaigns that were widely reported on in the newspapers of the times (Bijsterveld, 2003). A 1906 column in the Illustrated London News about the 'Nervous Age' reported that doctors were complaining to Parliament about the "injurious effects on the nervous system produced by the excessive noise of our streets" ( [Anon.…”
Section: The Poetics Of Noise In Italian Futurismmentioning
confidence: 99%
“…It is rooted in colonial ideology (that justified colonial domination in hierarchies of civilizedness) and, on a deeper level, in the old strategy of European elites to foster manners (Bourdieu's 'embodied cultural capital ' Bourdieu 1984, 70) as markers of status and justifications for class domination within Europe and colonial domination outside it (Elias 2000), framed in terms of culture versus nature (McClintock 1995). This identification of noise with those at the bottom of ethnic, national and class hierarchies, documented mainly for the nineteenth and early twentieth centuries (Bijsterveld 2001;Vaillant 2003), still prevails, although it is disregarded. In contemporary Israel, loudness and specific sonic practices are thus ethnicized, used simultaneously to bolster both national boundaries and ethnic hierarchies among Israeli Jews (often by comparing Mizrahi Jews to Arabs).…”
Section: O Schwarzmentioning
confidence: 99%
“…Such auditory practices were profoundly dislocated in the dawning of the mechanical age. In her study of noise abatement campaigns between 1900 and 1940, Bijsterveld (2003) highlights the extent to which manifestations of technology during this time drastically changed the sonic environment of Western societies. The ferocity of these campaigns evidences how profoundly disturbing industrial-era noise was, treated as a costly threat to the health and efficiency of urban citizens, which would surely "shorten the life of countless sufferers" (p. 174).…”
Section: Shifting Spaces I: Amplifying Modernitymentioning
confidence: 99%